Insulinoma-Associated Protein 1 Immunostain: A Diagnostic Tool for Pulmonary Small Cell Carcinoma in Cytology - Erika F. Rodriguez (2018)
© 2018 S. Karger AG, Basel Objective: Cytology plays an important role in the diagnosis of small cell carcinoma (SCLC). Application of immunohistochemical (IHC) markers improves the accuracy and reproducibility of the diagnosis of SCLC. We report the application of insulinoma-associated protein 1 (INSM1) in the diagnosis of SCLC in cytology samples. Methods: Our pathology data system was searched for SCLC where INSM1 IHC was performed. Patients’ demographics were recorded. Cytopathology specimens were reviewed. Results: A total of 32 cases were identified. INSM1 was positive in 31 (97%) cases. Twenty-seven cases showed a strong/diffuse pattern (84%). Four cases were focally/weak positive (13%). One case was negative (3%). the sensitivity of INSM1 for recognition of SCLC was 97%. CD56 was performed in SCLC. Twenty cases were strongly/diffusely positive (87%). One case was negative (4%). The sensitivity was 96%. Conclusion: INSM1 is positive in the majority of SCLC on cytology specimens and its sensitivity is similar to that of CD56 on SCLC. This has practical implications for the diagnosis of these tumors in cytology samples.